Reconceptualizing the Curriculum for Malaysian Advanced Nursing Education: An Outlook on Mechanical Ventilation Weaning Pedagogy - Norlidah Alias; Sakinah AwangHarun; Khairul Azhar Jamaludin (Frontiers Media S.A., 2022)
Although Advanced Nursing Education (ANE) in Malaysia is still in its early stages, the demand for skilled nurses, particularly those who can perform weaning processes from mechanical ventilation (WPMV), is increasing. These nurses, especially in the Cardiothoracic Intensive Care Unit (CICU) need to be equipped with critical thinking skills in order to make decisions on WPMV. However, the Malaysian ANE is still struggling to achieve this. Therefore, this paper is aimed at reconceptualizing the Malaysian ANE with a specific focus on the development of a Mechanical Ventilation Weaning Pedagogy framework. Building upon previous studies, relevant theories, and WPMV best practices outside Malaysia, this study proposed the development of a pedagogy based on four fundamentals: the Fundamental Pattern of Knowing, Curriculum Planning model, an ideal learning content for WPMV skills development, and local experts' opinions. The findings of this study can serve as a reference for stakeholders, nursing education providers, and relevant parties in improving the current ANE.